Mean Platelet Volume in Patients With Subclinical Hypothyroidism Attending at A Tertiary Care Hospital of Bangladesh - Hossain, Mohammad Afjal; Atiquzzaman, -; Sharifuzzaman, Mirza; Yasmin, Marufa; Siddiqui, Nazia Afrin; Amin, Farzana; Rahman, Mohammad Lutfar (Journal of Dhaka Medical College, 2023)
Background: Subclinical hypothyroidism (SCH) is a common endocrine disorder affecting about 3-8% of the general population. On the other hand, mean platelet volume (MPV) is an indicator of platelet activity, and elevated MPV is associated with adverse cardio-metabolic complications. This study was conducted to observe MPV in SCH and to correlate it with thyroid-stimulating hormone (TSH) and free thyroxine (FT4) levels. Materials and Methods: This cross-sectional observational study was conducted in Medicine and Endocrinology OPD of US- Bangla Medical College & Hospital over twelve (12) months from September 2020 to August 2021. This study included forty (40) cases of newly detected SCH and twenty (20) age & body mass index (BMI) matched euthyroid control subjects as per inclusion and exclusion criteria. Results: SCH group had higher TSH and MPV than controls (P value <0.001 and <0.05 respectively) where age, BMI, and FT4 level were comparable (P value>0.05). MPV shows a positive correlation with BMI in SCH & controls (P values <0.05). MPV shows a significant positive correlation with TSH and a negative correlation with FT4 only in SCH (P<0.05) but not in controls (P value>0.05). Conclusion: Patients with SCH have elevated MPV, so they are at increased risk of developing an adverse cardiovascular outcome. J Dhaka Med Coll. 2022; 31(1) : 61-65